Understanding Contextual Aspects of the Word ‘Look’ in Corpus of Contemporary American English: Semantics Study - Hani Rahmah; Ervina CM Simatupang (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2024)
This research investigates the contextual aspects and lexical semantics of the word "look" within the Corpus of Contemporary American English (COCA). By examining how "look" functions across different contexts, this study aims to uncover the multifaceted nature of its meaning and usage. The research is grounded in semantic theory, drawing on the works of Leech, and other prominent linguists to explore how meaning is constructed and conveyed through language. Key focuses include the categorization of "look" across various parts of speech, such as verbs, nouns, and interjections, and the examination of its idiomatic, non-idiomatic, and compositional meanings. The study employs a qualitative research methodology, analyzing linguistic data from COCA to identify patterns and themes in the usage of "look." This research aims to elucidate the complex interplay between context and meaning, offering insights into the cognitive processes involved in language comprehension and production. The findings highlight the significance of semantics in understanding language, particularly how specific words can convey a wide range of meanings depending on their contextual usage. Overall, this research contributes to the field of lexical semantics by providing a comprehensive analysis of the word "look," demonstrating its versatility and the intricate mechanisms by which meaning is negotiated in language. The research has implications for linguistic theory, language education, and the development of more precise language processing systems.